Analisis Pengaruh Pendapatan, Jumlah Anggota Keluarga dan Pendidikan Terhadap Pola Konsumsi Rumah Tangga Miskin di Desa Bebandem Karangasem - Sanjaya, I Komang Putra; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 8. Agustus 2017(pp.1395-1627), 2017)
This study aims to determine the effect simultaneously and partially between the variables of income, family size and education on consumption pattern of poor households in the Bebandem village. The population of the study were poor households in the Bebandem village, the sample is determined by the method of proportionate stratified random sampling because in this study population have a member or element that is not homogeneous and stratified proportional. The number of respondents according to the number of population is as much as 78 respondents. The analysis technique used in this research is multiple linear regression. The test results with SPSS show that: (1) income, number of family members and education positive and significant effect simultaneously the consumption pattern of poor households in the Bebandem village. (2) income, number of family members and education positive and significant effect partially on the consumption patterns of poor households in the Bebandem village. Things must be done by the Bebandem villagers is to improve education and the quality of its human resources so that income can be increased and consumption patterns, the better.
Keywords: Pendapatan, Jumlah Anggota Keluarga, Pendidikan, Pola Konsumsi